Aspects of Reproductive Biology of Flying Fish, Hirundichthys Oxycephalus (Bleeker, 1853) in Majene Waters, West Sulawesi Province, Indonesia - Nur, Muhammad; Muhammad Nur Ihsan; Wulan Ayuandiani; Adiara Firdhita Alam Nasyrah; Tenriware; Ady Jufri; Husain Latuconsina; Ahmad Muhtadi (Malaysian Journal of Science (MJS), 2025)
Flying fish (Family Exocoetidae) are small pelagic species with high commercial value and represent one of the main catches for local fishermen. Therefore, this study aims to explore the reproductive biology of flying fish, including the sex ratio, Gonad Maturity Index (GMI), Gonad Maturity Level (GML), and first gonad maturity size in Majene Waters, West Sulawesi Province. The study procedures were carried out for 1 year from October 2021 to September 2022. Sampling was performed at the flying fish fishing base in the Labuang and Somba areas, Mosso Village, Majene Regency, West Sulawesi Province. Data analysis was conducted at the Integrated Laboratory of the Fisheries Department, West Sulawesi University. During the study period, a total of 708 H. oxycephalus species were obtained, comprising 383 males and 325 females. The sex ratio of the samples in Majene Waters was imbalanced with a male-female ratio of 1.00:0.85. The Gonad Maturity Level found in the area was classified into various categories, including GML I (undeveloped), GML II (early development), GML III (mature gonad), GML IV (overdue development), and GML V (spawning). The spawning period was predicted to occur from March to July, with the highest peak in May. Furthermore, male fish reached gonad maturity at a size range of 19.94-20.60 mm with an average of 20.27 mm, which was earlier compared to females at 20.15-20.85 mm, with an average of 20.50 mm.